Dialogical spirit : Christian reason and theological method in the third millennium - Yong, Amos (James Clarke & Co., 2015)
Contemporary proposals for Christian theology from post-liberalism to Radical Orthodoxy and beyond have espoused their own methodological paradigms. Those who have ventured into this domain of theological method, however, have usually had to stake their claims vis-à-vis trends in what may be called the contemporary ""post-al"" age, whether of the post-modern, post-Christendom, post-Enlightenment, post-Western, or post-colonial varieties. This volume is unique among offerings in this arena in suggesting a way forward that engages on each of these fronts, and does so from a particularistic Chris.